2023
DOI: 10.1177/0958305x231220520
|View full text |Cite
|
Sign up to set email alerts
|

Does artificial intelligence promote green innovation? An assessment based on direct, indirect, spillover, and heterogeneity effects

Qiang Wang,
Tingting Sun,
Rongrong Li

Abstract: This paper investigates the intricate relationship between artificial intelligence (AI) and green innovation within the context of sustainable development goals. As societies strive to achieve sustainability, understanding the dynamics between technological advancements and environmental progress becomes paramount. Drawing from panel data encompassing 51 countries between 2000 and 2019, this study employs fixed-effects models, mediated effects models, and spatial Durbin models to meticulously examine the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…Besides, Lei et al [ 25 ] explore the connections between the EPT policy and corporate performance, focusing on innovation compensation, first-mover advantages, incentives for green transformation, and the relationship between technology and green transformation. Other studies have also shown that technological innovations and enhanced economic efficiency lead to green innovation and reductions in ecological footprints to improve green transformation [ 27 , 28 ]. Additionally, research focuses on the heterogeneity of the EPT policy's impact on corporate performance, primarily considering regional development levels, company size [ 2 ], and the nature of equity [ 23 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, Lei et al [ 25 ] explore the connections between the EPT policy and corporate performance, focusing on innovation compensation, first-mover advantages, incentives for green transformation, and the relationship between technology and green transformation. Other studies have also shown that technological innovations and enhanced economic efficiency lead to green innovation and reductions in ecological footprints to improve green transformation [ 27 , 28 ]. Additionally, research focuses on the heterogeneity of the EPT policy's impact on corporate performance, primarily considering regional development levels, company size [ 2 ], and the nature of equity [ 23 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies about the impact of ICTs on environmental challenges and carbon emissions are drawn from the literature and focus on the positive or negative ecological consequences of their expansion (Q Wang et al, 2023b). Similarly, the penetration of spillover characteristics of artificial intelligence (AI) forests environmental innovation, thereby achieving SDGs (Wang et al, 2024). Moreover, the growth of the financial sector has provided funding, venture capital, and loans for startups.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, researchers have explored the implications of various fiscal policies on green development, including income tax systems, budgetary decentralization, fiscal relations between governments, and the structure of fiscal expenditures. To prevent economic development from being trapped in a “low-carbon trap,” they also examine how budgetary policy interacts with other public policies, such as financial, environmental, industrial, and energy policies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%